Data rescue to extend the value of vintage seismic data: The OGS-SNAP experience. (June 2015) - Diviacco, Paolo; Wardell, Nigel; Forlin, Edy; Sauli, Chiara; Burca, Mihai; Busato, Alessandro; Centonze, Jacques; Pelos, Claudio
Abstract: Large amounts of vintage seismic data were rescued and disseminated in an internal project of the Istituto Nazionale di Oceanografia e di Geofisica Sperimentale (OGS). Such types of data would be very difficult to acquire today because they cover many areas that are currently subject to restrictions in obtaining exploration permits. The datasets extend over large geographical areas, covering large geological structures and would be very expensive to acquire today. Additionally, these data are particularly interesting because they were acquired using a high-energy source (dynamite) that would be difficult to obtain permission to use today. Therefore the recovery of these data could be very interesting for both the scientific and commercial communities. The urgency of rescuing tapes before degradation, and scanning and converting the paper sections into a usable form was the main focus, but, at the same time, the project looked ahead and attempted to address possible future exploitation of these data. To this end, considering how end users are likely to search for and use data, a full processing path that goes beyond recovery to consider other aspects was developed. The other concerns integrated into this process are data enhancement, to overcome data limitations due to the older technology used during acquisition; data integration, to consolidate different data types within the same data space, and data discovery, for which a specific web based framework named SNAP (Seismic data Network Access Point) was developed that allows end users to search, locate and preview the data.